Synthesis of African swine fever (ASF) virus-specific antibodies in vitro in a porcine leucocyte system. - Casal, I (1987)
We have developed a system of porcine peripheral blood mononuclear cells for the synthesis of antibodies in vitro, induced by partially purified African swine fever virus particles inactivated with formaldehyde. The antibodies synthesized were detected by a radioimmunoassay with a sensitivity of 3 ng of immunoglobulin. Primary responses were dependent on supernatants from peripheral blood mononuclear cells incubated with concanavalin A, macrophages and T lymphocytes. Secondary responses did not require concanavalin A-conditioned medium. The kinetics of antibody synthesis was similar in both primary and secondary responses, but the extent of synthesis was four to five times larger in the secondary than in the primary response. The antibodies synthesized in vitro were specific for African swine fever virus antigens (and did not react with viral antigen other than that from African swine fever virus particles), in contrast to pokeweed mitogen-induced antibodies, which reacted with all the antigens tested. African swine fever virus-induced antibodies did not neutralize the virus. These results and the inability of the virus to stimulate a primary response in the absence of concanavalin A supernatants indicate that inactivated African swine fever virus is not a polyclonal stimulator.